Question Card Game to Improve Senior High School Students' Higher-Order Thinking Skills in Biology Learning - Indria Wahyuni; Mukrimah Mukrimah; Faatihah Nasywaa Hanifah; Julianti Devi Ariesca; Windayanti Windayani (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
Technology development in the world of education will affect the existing curriculum. Whether or not an education is successful depends largely on the curriculum used. The curriculum is the spearhead for the implementation of education. In a curriculum, there are various supporting aspects. One of them is the learning model. Various learning models have been tried to develop student's thinking skills, for example, using the medium of question cards. Playing question card media can trigger direct student involvement in learning to increase high-level thinking skills and motivation to be more active in studying. This research is a Collective Action Research (RAC) study.